PENERAPAN SISTEM MANAJEMEN KEBERLANGSUNGAN BISNIS (BUSINESS CONTINUITY MANAGEMENT SYSTEM) DI PERUSAHAAN INDUSTRI SELAMA PANDEMI COVID-19 : KAJIAN LITERATUR - Ananda, Rizki; Djunaidi, Zulkifli (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
The COVID-19 pandemic which increased rapidly in early 2020 causes losses that can result in companies going out of business. To overce this, it is necessary to have a management system that manage continuity of the Business. Business Continuity Management System (BCMSS) is one of system management for employer to take an action a business continuity. However, there are still industries that have not implemented Business Continuity Management System (BCMS). Therefore, the purpose of this research is to see the difference in the impact of industries that apply and do not apply BCMS during the COVID-19 pandemic. This study uses the Preferred Reporting Items for Systematic Review & Meta-Analysis (PRISMA) method with inclusion criteria, namely articles that answer research, are published, use Indonesian or English, and were written in the last two years. The impacts on industries that implement BCMS are maintaining business continuity, returning to normal industrial conditions, mitigating disruptions, and reducing COVID-19 transmission. The impacts on industries that do not implement BCMS are labor problems, economic problems, and disruption of the supply chain. There is a significant difference between industries that implement BCMS and industries that do not apply BCMS where industries that apply BCMS can maintain business continuity.